Mobile Application for Credit Card Management: EZ Pay - Hishamuddin Abdul Wahab; Muhammad Miqdam Mohd Rashid; Rabiah Al-Adawiyah Ahmad Zabidi; Nur Laila Mohd Arif; Ahmad Shakir Ahmad Zulkifli; Muhammad Nor Amin Jamaluddin; Muhammad Nasrallah Abu Bakar (International Journal of Technical Research and Applications, 2024)
Nowadays, the widespread use of credit card without a proper management control especially among young generations in Malaysia has increased the chance of bankruptcy. In order to help society in prudent credit card management, this study proposes EZ Pay version 1.1 that basically adopts the concept of Easy Payment Plan (EPP) and developed on Android platform. The EZ Pay 1.1 is a combination of four apps which are Easy payment plan, credit card manager, calculator and card spending tracker. The EZ Pay version 1.1 is an upgraded mobile app from version 1.0 which is a credit management software to assist credit card holder in managing payment of credit card balance. EPP is a method of payment through credit card with 0% interest rate change with an upfront processing fee (varies for each bank) for a period of 12-36 months. The originality of this product lies on the way how we compile the information on the different processing fees of EPP across almost all Malaysian banks. This product educates users on the usefulness of EPP that is simply developed on a mobile platform. This software has an ability to encourage wise spending habit among users with a greater practically at your fingertips.